Spectral effect of streetlamps on urban trees: A simulated study on tissue water, nitrogen, and carbohydrate contents in maple and oak. - Ping Liu; Baohui Cao; Yutao Wang; Zhongping Wei; Jingfeng Ye; Hongxu Wei (PLoS ONE)
Streetlamps enforce night lighting on urban forest trees, but scarce information is available concerning the ecophysiological performance of street trees under these conditions. In this study, maple (Acer truncatum Bunge) and oak (Quercus mongolica Fisch. ex Ledeb.) seedlings were cultured with simulated exposure to streetlamp spectra in white (red/green/blue, 7.7:1.0:2.2) and red plus blue (RB; red/green/blue, 4.6:0.0:1.0) lights with photosynthetic photon flux rate of 80 μmol m-2 s-1 in a 18-h photoperiod. Nitrogen (N) was loaded through 15 weekly applications to an amount of 80 mg N plant-1 to mimic the mineral N deposition to landscape trees. Variables of biomass, carbohydrate accumulation, N and water contents were rarely found difference between the two LED-spectra treatments for both species. Compared to the un-lighted control, the RB spectrum lowered N concentration in oak seedlings and water content in maple seedlings. The white light spectrum resulted in an increase of starch concentration. Carbohydrate concentration had a positive relationship with biomass and N content across two species but a negative relationship with water content in maple seedlings. Overall, streetlamp-lights imposed effects on tree growth by a prolonged photoperiod instead of specific spectrum. Maple had a strong response of water uptake to streetlamp lighting at the cost of carbohydrate consumption, but oak had scarce demand of water-use for growth.